Low-Dose Quetiapine Improves Symptoms of Borderline Personality Disorder - Parry, Nicola (MD Conference Express, 2014)
Although no drugs are currently approved for treatment of borderline personality disorder (BPD), studies have shown the benefit of antipsychotic agents for this indication, particularly when symptoms of mood instability, anger and irritability, and self-harm are prominent. Open-label studies have demonstrated that the atypical antipsychotic drug quetiapine is efficacious and well tolerated in treating these patients. This article presents results of a placebo-controlled trial demonstrating that low doses of long-acting quetiapine significantly improve symptoms in patients with BPD.